Facial Protection to Prevent Facial Trauma and Allow for Optimal Protection after Facial Fracture Repair - Kim, Roderick; Shokri, Tom; Wang, Weitao; Ducic, Yadranko (Facial Plastic Surgery, 2021)
Facial skeletal fractures continue to affect humankind, and many methods to alleviate and prevent the injuries outright have been sought after. Prevention is desired, but the implementation and general compliance may contribute to missed opportunities to decrease the burden of facial skeletal trauma. In this article, we explore the preventative as well as postoperative options for the protection of the facial skeleton.
Keywords: facial trauma; maxillofacial trauma; facial protection; CMF trauma; postoperative protection